Overcoming Implicit Meaning in Indonesian-English Translation - Made Susini (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
Implicit meaning is one of the language phenomena which need overcoming in translation. This present study aims to investigate in what construction the implicit meaning is realized in Indonesian and how implicit meaning is handled when it is rendered into English. This study applied a descriptive qualitative approach. The data were taken from a book of Indonesian short stories entitled Mandi Api (Soethama, 2006) and its translation in English entitled Ordeal by Fire (Cork, 2008). The results of the research showed that implicit meaning in Indonesian texts is conveyed into English in two ways. Firstly, the implicit meaning is kept implicit. Secondly, it is realized in explicit construction. The implicit information of the source texts is made explicit in target texts for some reasons which include grammatical reason, semantic reason, and stylistic reason. In conclusion, although the source and the target texts have different constructions in the translation under study, the source meanings are successfully conveyed into English.